The determinant of profitability of foreign commercial banks in Malaysia - Theyvi, Atchuthan (2018)
This research is conducted to determine the profitability of foreign commercial banks in Malaysia based on five factors which are bank size, loan to asset ratio, inflation rate, interest rate, and the Gross Domestic Product, (GDP). An intensive desk research is conducted as measure to determine the present issue related to foreign commercial bank profitability in Malaysia. It is found that as of January 2018, there are 28 commercial banks in Malaysia. Nevertheless, this research focused on ten foreign commercial banks operating in Malaysia. Furthermore, this study utilise secondary data as the main source of information in conducting the analysis in this research. The data are extracted mainly from the income statement and also balance sheet in the annual report of each respective foreign commercial bank operating in Malaysia for the period of 2007 to 2016. Based on the analysis computed via SPSS statistical software application, this study suggested that the profitability of foreign commercial banks in Malaysia is influenced by bank-specific determinants which is bank size, loan to asset ratio, and interest rate while the macroeconomic determinants which is GDP and Inflation rate are considered as not significant towards return on asset of the foreign commercial banks.